Breast cancer surgery in patients with schizophrenia: short-term outcomes from a nationwide cohort. Issue 2 (4th January 2021) - Konishi, T; Fujiogi, M; Michihata, N; Tanaka-Mizutani, H; Morita, K; Matsui, H; Fushimi, K; Tanabe, M; Seto, Y; Yasunaga, H
Abstract: Background: Although patients with schizophrenia have a higher risk of developing breast cancer than the general population, studies that have investigated postoperative complications after breast cancer surgery in patients with schizophrenia are scarce. This study examined associations between schizophrenia and short-term outcomes following breast cancer surgery. Methods: Patients who underwent surgery for stage 0–III breast cancer between July 2010 and March 2017 were identified from a Japanese nationwide inpatient database. Multivariable analyses were conducted to compare postoperative complications and hospitalization costs between patients with schizophrenia and those without any psychiatric disorder. Three sensitivity analyses were performed: a 1 : 4 matched-pair cohort analysis with matching for age, institution, and fiscal year at admission; analyses excluding patients with schizophrenia who were not taking antipsychotic medication; and analyses excluding patients with schizophrenia who were admitted to hospital involuntarily. Results: The study included 3660 patients with schizophrenia and 350 860 without any psychiatric disorder. Patients with schizophrenia had a higher in-hospital morbidity (odds ratio (OR) 1.37, 95 per cent c.i. 1.21 to 1.55), with more postoperative bleeding (OR 1.34, 1.05 to 1.71) surgical-site infections (OR 1.22, 1.04 to 1.43), and sepsis (OR 1.20, 1.03 to 1.41). The total cost of hospitalization (coefficient €743, 95 per cent c.i. 680 to 806) was higher than that for patients without any psychiatric disorder. All sensitivity analyses showed similar results to the main analyses. Conclusion: Although causal inferences remain premature, multivariable regression analyses showed that schizophrenia was associated with greater in-hospital morbidity and higher total cost of hospitalization after breast cancer surgery than in the general population. Abstract : This study aimed to investigate the associations between schizophrenia and short-term outcomes after breast cancer surgery, using a Japanese nationwide inpatient database. Multivariable regression analyses showed that having schizophrenia was associated with greater in-hospital morbidity (including postoperative bleeding, surgical-site infection, and sepsis) and higher total cost of hospitalization than in the general population. Vulnerable patient group